A139 AGREEMENT OF IBDOC® AND QUANTON CAL® RAPID LATERAL FLOW-BASED FECAL CALPROTECTIN TESTS WITH ACCEPTED LAB-BASED ASSAYS FOR MONITORING INFLAMMATORY BOWEL DISEASE. (1st March 2018) - Sutton, R T; Prosser, C; Dhami, N; Sadowski, D; van Zanten, S; Kroeker, K I; Wong, K; Halloran, B P; Fedorak, R; Huang, V
Abstract: Background: Fecal calprotectin (FCP) is a useful biomarker for monitoring inflammatory bowel disease, showing good correlation to endoscopic disease activity. Currently used lab tests take 2–4 weeks to return a result, limiting their usefulness. Recently, lateral flow-based rapid tests have been combined with smartphone applications to allow patients to complete FCP testing at home, with their physician receiving the result the same day. Aims: We aim to compare FCP results from two point-of-care test (POCT) devices (IB Doc ; Buhlmann, Quanton Cal ; Preventis) in real world use, to two widely accepted lab based methods. Methods: Patients brought first morning stool to the University of Alberta IBD clinic, completed partial Mayo (pMayo) and Harvey-Bradshaw index (mHBI) scores, received training, and performed the IB Doc test. A portion of their raw sample was sent to the hospital lab, stored at -20°C, thawed and then analyzed using Quanton Cal POCT kits (performed by laboratory staff) and two weight-based lab tests: Immunodiagnostik (ELISA) and Buhlmann Turbo (immunoturbidimetric) assays. Numerical FCP values were tabulated and dichotomized by ≥250 µg/ml (active) or <250 µg/ml (remission). Clinical scores were dichotomized as symptomatic if mHBI≥5 or pMayo≥2. Results: Twenty patients provided raw stool and completed the IB Doc test, including 12 (60.0%) females and 9 (45.0%) with Crohn's disease. The median age is 33.5 years (IQR: 29.5 to 37.5). Maintenance medications: 3 (15.0%) taking no medications, 4 (20.0%) on 5-ASA, 4 (20.0%) on immunomodulators, 9 (45.0%) on biologics, of whom 3 (15.0%) were on biologic combotherapy. Median FCP values and IQRs for all four tests are shown in Figure 1. Spearman's correlation with results from Immunodiagnostik was 0.93 for IB Doc, 0.89 for Quanton Cal, and 0.97 for Buhlmann Turbo. Upon dichotomizing FCP as active or inactive, 18/20 (90%) of results were in agreement between IB Doc and Immunodiagnostik, 19/20 (95%) between Quanton Cal and Immunodiagnostik, and 19/20 (95%) between IB Doc and Quanton Cal . However; pMayo/mHBI and FCP were not as agreeable with 12/20 (60%) reaching the same conclusion (symptomatic or asymptomatic) for IB Doc, 13/20 (65%) for Quanton Cal, and 14/20 (70%) for Immunodiagnostik. Conclusions: There is good correlation between POCTs and lab tests at <250 µg/ml, although correlation was better between the two lab tests. POCTs can differentiate disease activity from remission and can be performed remotely, an advantage for rural patients. The quantitative values >250 µg/ml are not reproducible and would be misleading if used to monitor disease progression . FCP close to cutoffs should be repeated and does not correlate very well with patient reported symptoms. Funding Agencies: None